Analisis Ayat Al-Qur’an: Pendekatan Penyampaian Argument Logis dan Estetika : (Kajian Madzhab Kalami dan Husnul Ta’lil) - Sartika Alpianti Manurung; Ja’alna Salwinur Baeha; Harun Al-Rasyid (STIKes Ibnu Sina Ajibarang, 2025)
This article discusses two discussion materials in the science of badi' muhassinat ma'nawiyah study. The first discussion is about analyzing the meaning of madzhab kalami in one of the verses of the Qur'an, namely in surah Al-Anbiya' verse 22, surah Al-Hajj verse 5 and surah Ar-Ruum verse 27. While the second discussion is about husnul ta’lil in three other surahs, namely surah Al-Baqarah verse 74 and 261 and surah An-Nahl verse 14. The research method used in this study is a qualitative research method with literature review (library research) as the data collection technique. The results of this study are, the discovery of the purpose and purpose of the meaning of madzhab kalami in surah Al-Anbiya' verse 22, surah Al-Hajj verse 5 and surah Ar-Ruum verse 27, as well as the meaning of husnul ta’lil in surah Al-Baqarah verse 74 and 261 and surah An-Nahl verse 14.